2007
DOI: 10.1007/s00101-007-1226-5
|View full text |Cite
|
Sign up to set email alerts
|

Primingtechnik mit Cisatracurium

Abstract: Our results show that only high dose priming of cisatracurium can significantly shorten the laryngeal onset time. However, clinical routine use is not recommended due to possible side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thus, we have to pay attention to decide the priming dose. No adverse effects were reported in recent studies that used a priming dose of cisatracurium 0.01 mg/kg [9,16,19]. Schmidt et al [19] demonstrated that high dose of priming of cisatracurium was effective to shorten the onset time of cisatracurium, but did not not recommended clinical routine use due to possible side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we have to pay attention to decide the priming dose. No adverse effects were reported in recent studies that used a priming dose of cisatracurium 0.01 mg/kg [9,16,19]. Schmidt et al [19] demonstrated that high dose of priming of cisatracurium was effective to shorten the onset time of cisatracurium, but did not not recommended clinical routine use due to possible side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…No adverse effects were reported in recent studies that used a priming dose of cisatracurium 0.01 mg/kg [9,16,19]. Schmidt et al [19] demonstrated that high dose of priming of cisatracurium was effective to shorten the onset time of cisatracurium, but did not not recommended clinical routine use due to possible side-effects. In our study, we used the same priming dose and priming interval as in Schmidt's study (cisatracurium 0.01 mg/kg, 3 minutes) and our findings were similar from Schmidt et al [19].…”
Section: Discussionmentioning
confidence: 99%